Opening the black box of traumatic brain injury: a holistic approach combining human 3D neural tissue and an in vitro traumatic brain injury induction device - Loussert-Fonta, Céline; Stoppini, Luc; Neuenschwander, Yoan; Righini, Ophélie; Prim, Denis; Schmidt, Cédric; Heuschkel, Marc O.; Gomez Baisac, Loris; Jovic´, Milica; Pfeifer, Marc E.; Extermann, Jérôme; Roux, Adrien (Frontiers in Neuroscience, 2023)
Traumatic brain injury (TBI) is caused by a wide range of physical events and can induce an even larger spectrum of short- to long-term pathophysiologies. Neuroscientists have relied on animal models to understand the relationship between mechanical damage and functional alterations of neural cells. These in vivo and animal based in vitro models represent important approaches to mimic traumas on whole brains or organized brain structures but are not fully representative of pathologies occurring after traumas on human brain parenchyma. To overcome these limitations and to establish a more accurate and comprehensive model of human TBI, we engineered an in vitro platform to induce injuries via the controlled projection of small drop of liquid onto a 3D neural tissue engineered from human iPS cells. With this platform, biological mechanisms involved in neural cellular injury are recorded through electrophysiology measurements, quantification of biomarkers released and two imaging methods (CLSM and OPT). Obtained results showed drastic changes in tissue electrophysiological activities as well as significant releases of glial and neuronal biomarkers. Tissue imaging allowed to reconstruct the injured area spatially in 3D after staining it with specific nuclear dyes and to determine TBI resulting cell death. In future experiments, we seek to monitor the effects of TBI-induced injuries over a prolonged time and at a higher temporal resolution to better understand the subtleties of the biomarker release kinetics and the cell recovery phases.